An analysis of existential feminism on Bombshell (2019) movie - Niken Ayu Lestari; Diana Aggraeni; Tri Arie Bowo (Universitas Aki, 2023)
Feminism existentialists focus on women's existence as an object for men. This study analyzes existential feminism in Bombshell movie, released in 2019, written by Charles Randolph and directed by Jay Roach. This study used existentialist feminism by Simone de Beauvoir. The study aims to discover how women exist as